The Legal Status of Cemevis: Culture or Belief? An Analytical Reflection on Lost Centuries (Journal of Alevism-Bektashism Studies, 2023)
1461 years have passed since the death of the 4th Caliph Ali, both of his sons were killed and the caliphate in Islam, at that time, was passed from one tribe to another tribe. The fact that these events took place within 30 years created great trauma and deep divisions for the beginning years of religion. Although the situation is the same in all geographical regions where Islam has spread, it has revealed different forms of belief and worship. Those who follow the path of Hazrat Ali with the motto of “Haqq-Muhammad-Ali” have survived to this day with moral rumors and slanders in their daily and family lives, while being discriminated against mostly politically and sometimes religiously over long centuries. While the Alevi faith community was an uneducated mass before, it started to urbanize with the proclamation of the Republic. As the education levels increased, they expressed in writing and orally that instead of mosques, the place of worship following their beliefs and customs was Djemevis based on equal citizenship and that the state should meet this. Like the Alevis and Sunni masses, they demand a share from a common state budget, to be secured, to be represented, and to legally institutionalize their faith communities. The belief community in question provided great support in the War of Independence as well as keeping the Turkish language alive in Anatolia for centuries. In this article, the political and religious drifts of the Alevi faith communities within the historical chronology are examined and the solution proposals regarding the different models of the unresolved legal structure of the Djemevi and their possible benefits are put forward in practice, not in theory.